2016
DOI: 10.1021/acs.jafc.6b00675
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Novel Auxin Mimic Herbicides

Abstract: Due to the key roles of auxins as master regulators of plant growth, there is considerable interest in the development of compounds with auxin-like properties for growth management and weed control applications. Herein, we describe the design and multistep synthesis of ten compounds bearing combinations of functional groups commonly associated with auxin-type properties. Following synthesis, these compounds were tested against multiple weed species as well as sweet corn. In general, while these structures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…This result indicates that the free carboxyl group of JA-Ile is not essential for this molecule to induce JRG expression [85,86]. Similar outcomes were observed in other studies, so systematic structural modifications of JA revealed the minimal structural requisites required for its bioactivity allowing for the synthesis of JA-mimics [85,89,90].…”
Section: Design and Synthesis Of Molecules For The Exogenous Stimulation Of Receptorssupporting
confidence: 69%
See 1 more Smart Citation
“…This result indicates that the free carboxyl group of JA-Ile is not essential for this molecule to induce JRG expression [85,86]. Similar outcomes were observed in other studies, so systematic structural modifications of JA revealed the minimal structural requisites required for its bioactivity allowing for the synthesis of JA-mimics [85,89,90].…”
Section: Design and Synthesis Of Molecules For The Exogenous Stimulation Of Receptorssupporting
confidence: 69%
“…AUXs could be called the "Master of Plant Growth" and are one of the most widely studied plant hormones. There are four natural auxins that are synthesized by plants: indole-3-acetic acid (IAA), indole-3-butyric acid (IBA), 4-chloroindole-3-acetic acid (4-Cl-IAA), and phenylacetic acid (PAA) [89,90] (Figure 4).…”
Section: Design and Synthesis Of Molecules For The Exogenous Stimulation Of Receptorsmentioning
confidence: 99%
“…Indoles are one of the most prominent heteroaromatic motifs due to their widespread presence in biologically significant natural compounds, pharmaceuticals, and agrochemicals . In particular, substituted indoles are generally known as “privileged scaffolds” because of their ability to bind many receptors with strong affinity .…”
Section: Introductionmentioning
confidence: 99%
“…Several potential issues need to be addressed: (1) the Chan-Lam arylation has been extended to numerous nucleophilic partners for carbonheteroatom bonds formation, 32 but not to enamines. (2) The Chan-Lam N-arylation involving arylboronic acids is known to occur in the presence of Cu(II) catalyst, while the Cu(I) catalyst has usually been employed in the C-H functionalization step. 9,30 Merging fundamentally different copper catalysis into one-pot reaction is still challenging.…”
Section: Introductionmentioning
confidence: 99%